Gelar Karya Sebagai Upaya Penguatan Public Speaking Mahasiswa Program Studi KPI IAIN Kudus - Zykratul Rahma, Alya; Rohimi, Primi (Journal Proxemics, 2024)
The purpose of this study is to determine the effectiveness of gelar karya as an effort to strengthen public speaking skills for students of the Islamic Broadcasting Communication (KPI) study program at IAIN Kudus. This research employs a qualitative approach with data collection techniques including in-depth interviews, participatory observation, and documentation. The collected data undergoes a process of reduction, interpretation, and conclusion drawing to explore how gelar karya contributes to strengthening students' public speaking skills. The research findings indicate that gelar karya plays a significant role in training students to appear confident in public, although many still experience anxiety. In conclusion, gelar karya is an effective means of strengthening public speaking skills for KPI students at IAIN Kudus. It is not only beneficial in an academic context but also crucial in equipping students with essential communication skills needed in the professional world.